Grandma's hospital - McCartney, Jenny; Bruere ,Julian (Illustrator) (Santa Rosa, CA: SRA School Group., 1994)
As Grandma gradually repairs all the other toys that need mending, Kate continues to insist that she likes her teddy just the way he is, with one eye missing.
Keywords: English, Fiction